Study of the Biochemical Markers of Liver and Renal Function in Moderate -To- Heavy Cigarette Smokers’ Men in Mosul City - Enaam Ahmed Hamza Al-Dagestani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Smoking has been associated with adverse health effects on body organs. The effect of smoking on theliver’s enzymes and kidney’s parameters, and their relationships with some blood parameters need moreevaluation. This study aimed to investigate the association of cigarette smoking to liver and kidney functionsin 68 males, all of them not suffer from chronic disease and their ages were between (25-45) years, byestimating the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkalinephosphatase (ALP) as liver enzymes as well as estimating of creatinine, urea, and uric acid in the serumof smokers comparing with non-smokers groups (control). Also, this work aimed to study the effects ofsmoking on some blood profiles, white blood cell counts (WBC), red blood counts (RBC), hemoglobin(HB), mean corpuscular volume (MCV), and platelet (PLT) . The results showed a significant increase in(ALT), (AST), (ALP) enzymes, urea, creatinine (WBC), (RBC), (HB) and (MCV) ,the result also showeda significant decrease in uric acid while no significant decrease in (PLT) in smokers comparing to nonsmokers’ group. In conclusion a cigarette smoking negatively affected in biochemical markers of liver andkidney function.